Bolstering Indonesia's Urban Government Finance: Lessons from Extended Crises - Jhonny Patta; . Pradono (The Institute for Research and Community Services, Institut Teknologi Bandung, 2004)
This paper examines the possibility for urban governments in Indonesia to bolster their finance in response to the decline in national government finance due to extended crisis, as well as the policy towards local autonomy & decentralization. Derived from local public finance literature, it is argued that there are at least three approaches viable to be implemented by local government to bolster their finance namely intensive revenue mobilization, engineered efficiency improvements, and expenditure responsibility contraction. We explore the possibility of each approach to be implemented to local government within the context of socio-political setting in Indonesia. Though we haven't come to judge which approach is the best implemented, as it may come to be case & local specific, we note the importance of private role that could be played in all approaches.